2010
DOI: 10.2169/internalmedicine.49.2731
|View full text |Cite
|
Sign up to set email alerts
|

A Right Paratracheal Air Cyst Caused by Tracheal Diverticula

Abstract: A 65-year-old

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 12 publications
0
28
0
Order By: Relevance
“…In our study, which contained the largest number of patients evaluated thus far, we observed PACs in 4.0% of the patient group. In some cases, PACs may be symptomatic due to a local mass effect and direct compression, resulting in clinical manifestations such as a chronic cough, repeated episodes of respiratory infections, haemoptysis, stridor, dysphagia, chest‐neck and/or right clavicle pain or dyspnoea . Rarely, a large diverticulum can compress the recurrent laryngeal nerve and result in dysphonia .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, which contained the largest number of patients evaluated thus far, we observed PACs in 4.0% of the patient group. In some cases, PACs may be symptomatic due to a local mass effect and direct compression, resulting in clinical manifestations such as a chronic cough, repeated episodes of respiratory infections, haemoptysis, stridor, dysphagia, chest‐neck and/or right clavicle pain or dyspnoea . Rarely, a large diverticulum can compress the recurrent laryngeal nerve and result in dysphonia .…”
Section: Discussionmentioning
confidence: 99%
“…To avoid confusing PACS and pneumomediastinum, in our study, we excluded patients who had undergone tracheotomy, intubation, sternotomy and trauma. In addition to pneumomediastinum, differential considerations for PACs include pharyngocele, laryngocele, Zenker diverticulum, apical lung hernia, blebs and bulla . Contrast esophogram and cervical and thoracic CT are useful, non‐invasive examinations for narrowing the differential diagnostic considerations in these patients.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This was followed by Chiari's 1889 description of six autopsies with diverticula at the lower end of the trachea on the right side (MacKinnon, ). Present day sources describe a tracheal diverticulum as a benign entity characterized by single or multiple outpouchings of the tracheal wall (Sato et al, ). According to an autopsy series of 867 specimens, MacKinnon () estimated an overall prevalence of tracheal diverticula at about 1%.…”
Section: Tracheal Diverticulummentioning
confidence: 99%
“…In contrast, acquired tracheal diverticula appear laterally between the cartilaginous rings or posterolaterally through the trachealis muscle (Restrepo et al, ; Desir and Ghaye, ; Sato et al, ). The more common posterolateral diverticula are usually located on the right side at the level of the thoracic inlet (Restrepo et al, ; Desire and Ghaye, ; Sato et al, ). The development of acquired tracheal diverticula is the result of mucosal herniation through a weak point in the tracheal wall (Goo et al, ).…”
Section: Tracheal Diverticulummentioning
confidence: 99%